A STUDY OF COOPERATIVE LEARNING STAD IN REDUCING EFL STUDENTS’ SPEAKING ANXIETY - Savira, Alifia; Setyaningsih, Tri; Burhayani, Burhayani (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Recognizing the presence of Foreign Language Speaking Anxiety (FLSA), numerous educators have endeavoured to implement various strategies to mitigate this challenge. Student Team Achievement divisions (STAD) is one of cooperative learning strategies that requires small groups of students with various levels of competence to collaborate and achieve a common learning objective. This study aims to find out what factors causing Foreign Language Speaking Anxiety in EFL classrooms and describe how Cooperative Learning STAD reduce EFL’ students speaking anxiety. This study is a mixed method research which combines qualitative and quantitative data through three-day-reflective observation checklists and closedended questionnaire. The main participants in this study were students of eleven grade Accountant student 2 at Vocational High school in Jakarta with the total of 37 students. The result of this study showed that students experienced anxiety due to various factors including interpersonal, personal anxiety, beliefs about learning a foreign language, fear of mistakes, and language exams. It should be noted, using STAD, which includes teaching, team study, testing, and recognition, helped students to improve their understanding, speaking skills, and confidence. Thus, this study concluded that Cooperative Learning STAD significantly reduced students' speaking anxiety. Keywords: Cooperative Learning STAD, FLSA, EFL, Speaking Anxiety